Mechanical analysis of concrete using over-burnt bricks as coarse aggregate - Mantari Ramos, Yober Ostherlen (2025)
The purpose of the project is to experimentally evaluate the properties of concrete in a hardened state when the coarse aggregate is replaced in dosages by over - burnt crushed bricks obtained from the artisanal brick kilns in the city of Huancay o. This material was chosen due to the abundance of artisanal brick kilns in the area, which gener ates waste in its preparation polluting the environment, so this material was used in order to give it an added value and improve the properties of concrete. To fulfill the objective of the research, the mechanical properties of the concrete were determined in the laboratory, compressive strength tests, tensile strength tests and flexural strength tests at 28 days were carried out in dosages of 5%, 10% and 15% of over - burnt crushed brick using a mix design of 210 kg/cm² with the ACI method. It was determined that the percentage of 10% was the one that provided the highest compressive strength with a value of 323.54 kg/cm², likewise a tensile strength of 24.89 kg/cm² was achieved with the same percentage; with respect to flexural strength, a maximum of 65.39 kg/cm² was achieved with a 5% replacement. It was recommended to use 10% of over - burnt crushed bricks since this was the optimum percentage to improve the mechanical properties of the hardened concrete based on the standard sample.